Library Strategies In Developing Children's Reading Interest (Case Study Of The Seberang Belawan Fisherman Village Floating Library) - Asmaul Husnah; Abdul Karim Batubara; Anang Anas Azhar (Pena Cendekia Insani, 2022)
Interest in reading is a strong desire accompanied by one's efforts to read. The purpose of this study was to find out how the strategy for developing children's reading interest in the Floating Library of Seberang Belawan Fisherman Village. The study used a qualitative descriptive approach, using data collection techniques through observation, interviews and documentation. The results of this study indicate that the strategies used by the Floating Library in developing the reading interest of the children of the fishing village are; Learning with floaters, literacy activities, drawing, scholarship selection programs, volunteer development programs, Commemorating major holidays giving gifts in the form of snacks to children after completing activities, this is done so that children are motivated in carrying out the learning process at the Floating Libraries. Obstacles faced by volunteers at the Floating Library are that they only operate for one day a week, the service schedule is less effective to develop interest in reading for children from fishing villages, lack of facilities, isolated areas, lack of volunteer loyalty so that changes in library strategy in developing children's reading interest in The fishing village across Belawan occurred significantly, this is evidenced by the results of data analysis which stated that the increasing number of children participating in the learning program from 2014 was 20 students until now in 2020 there are 60 students in the Floating Library of the Seberang Belawan Fisherman Village.